Parental exposure to environmental concentrations of diuron leads to aneuploidy in embryos of the Pacific oyster, as evidenced by fluorescent in situ hybridization - Barranger, Audrey; Benabdelmouna, Abdellah; Degremont, Lionel; Burgeot, Thierry; Akcha, Farida (Aquatic Toxicology, 2015)
International audience